Clinical relevance and practical implications of trials of perfusion and angiographic imaging in patients with acute ischaemic stroke: a multicentre cohort imaging study. Issue 9 (3rd May 2013) - Wardlaw, Joanna M; Muir, Keith W; Macleod, Mary-Joan; Weir, Christopher; McVerry, Ferghal; Carpenter, Trevor; Shuler, Kirsten; Thomas, Ralph; Acheampong, Paul; Dani, Krishna; Murray, Alison
Abstract : Background: In randomised trials testing treatments for acute ischaemic stroke, imaging markers of tissue reperfusion and arterial recanalisation may provide early response indicators. Objective: To determine the predictive value of structural, perfusion and angiographic imaging for early and late clinical outcomes and assess practicalities in three comprehensive stroke centres. Methods: We recruited patients with potentially disabling stroke in three stroke centres, performed magnetic resonance (MR) or CT, including perfusion and angiography imaging, within 6 h, at 72 h and 1 month after stroke. We assessed the National Institutes of Health Stroke Scale (NIHSS) score serially and functional outcome at 3 months, tested associations between clinical variables and structural imaging, several perfusion parameters and angiography. Results: Among 83 patients, median age 71 (maximum 89), median NIHSS 7 (range 1–30), 38 (46%) received alteplase, 41 (49%) had died or were dependent at 3 months. Most baseline imaging was CT (76%); follow-up was MR (79%) despite both being available acutely. At presentation, perfusion lesion size varied considerably between parameters (p<0.0001); 40 (48%) had arterial occlusion. Arterial occlusion and baseline perfusion lesion extent were both associated with baseline NIHSS (p<0.0001). Recanalisation by 72 h was associated with 1 month NIHSS (p=0.0007) and 3 month functional outcome (p=0.048), whereas tissue reperfusion, using even the best perfusion parameter, was not (p=0.11, p=0.08, respectively). Conclusion: Early recanalisation on angiography appeared to predict clinical outcome more directly than did tissue reperfusion. Acute assessment with CT and follow-up with MR was practical and feasible, did not preclude image analysis, and would enhance trial recruitment and generalisability of results.